Scoping Review: Relationship between Overweight and Obesity with Triple Negative Breast Cancer in Woman - Dian Alfiani Theona; Widayanti Widayanti; Mirasari Putri (Jurnal Integrasi Kesehatan dan Sains, 2022)
Breast cancer is still one of the main problems for global public health. Breast cancer has several pathological characteristics, including triple negative breast cancer (TNBC) characterized by negative ER, PR, HER2 results and has a poor prognosis. Risk factors for TNBC are closely related to Body Mass Index (BMI) as an individual description of obesity. It is known in women, overweight and obesity can trigger breast cancer. This study aims to analyze the relationship between overweight and obesity based on BMI with the incidence of TNBC in women. This study used a scoping review to analyze scientific writings from three data sources, they are PubMed, ScienceDirect and SpringerLink. In the initial search, 797 articles were generated, then adjusted according to the inclusion, exclusion and eligibility criteria to produce 5 articles summarized in the PRISMA diagram. Of the five articles that were predominantly conducted in Asia, four articles stated that women with a BMI ≥25 kg/m2 had a higher risk of TNBC. One article stated that the risk factors for TNBC can be assessed from waist circumference other than BMI. In addition, there is one article that mentioned the opposite, there is no relationship between BMI at the age of 25-54 years and TNBC. The conclusion of this study is that obesity have a relationship with the incidence of TNBC in women.